Influência do cloro, sôbre a composição do caldo da cana de açúcar Co 290, aplicado no solo, na forma de cloreto de sódio - Moraes, J. Mello; Almeida, J. R.; Coury, T.; Gomes, F. Pimentel; Valsechi, O.; Ranzani, G.; Kiehl, E. J. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1950)
Considering the economic importance of the sugar industry among ourselves, the authors carried out a field experiment (Latin square) with Co 290 sugar cane, on a white sandy soil of Piracicaba, State of São Paulo, Brazil, applying NaCl in increasing rates (from 6.8 to 54.5 grams per plant), in order to study the effects of chlorides, on productivity and on the composition of juice. No toxic or stimulating effect was found, and there was no change in yield, in degree of purity of the juice, in general aspect of plants or in colour of leaves and culms. No difference was observed between potassium sulphate or chloride, as source of potash for sugar cane culture. Data collected and the literature cited suggest: (a) that the use of the variety Co 290 is indicated for soils rich in chlorine, such as the saline soils of the North-east and Atlantic Coast of Brazil; (b) that it is necessary to extend studies in Research Institutes and Agricultural Experiment Stations of the country to verify the behaviour of other varieties of sugar cane in the types of soils mentioned, especially with respect their yielding capacity. The authors are already planning such investigations.